The newly developed CRF1-receptor antagonists, NGD 98-2 and NGD 9002, suppress acute stress-induced stimulation of colonic motor function and visceral hypersensitivity in rats. - Mulugeta Million; Jing-Fang Zhao; Andrew Luckey; József Czimmer; George D Maynard; John Kehne; Diane C Hoffman; Yvette Taché (PLoS ONE, 2013)
Corticotropin releasing factor receptor 1 (CRF1) is the key receptor that mediates stress-related body responses. However to date there are no CRF1 antagonists that have shown clinical efficacy in stress-related diseases. We investigated the inhibitory effects of a new generation, topology 2 selective CRF1 antagonists, NGD 98-2 and NGD 9002 on exogenous and endogenous CRF-induced stimulation of colonic function and visceral hypersensitivity to colorectal distension (CRD) in conscious rats. CRF1 antagonists or vehicle were administered orogastrically (og) or subcutaneously (sc) before either intracerebroventricular (icv) or intraperitoneal (ip) injection of CRF (10 µg/kg), exposure to water avoidance stress (WAS, 60 min) or repeated CRD (60 mmHg twice, 10 min on/off at a 30 min interval). Fecal pellet output (FPO), diarrhea and visceromotor responses were monitored. In vehicle (og)-pretreated rats, icv CRF stimulated FPO and induced diarrhea in >50% of rats. NGD 98-2 or NGD 9002 (3, 10 and 30 mg/kg, og) reduced the CRF-induced FPO response with an inhibitory IC50 of 15.7 and 4.3 mg/kg respectively. At the highest dose, og NGD 98-2 or NGD 9002 blocked icv CRF-induced FPO by 67-87% and decreased WAS-induced-FPO by 23-53%. When administered sc, NGD 98-2 or NGD 9002 (30 mg/kg) inhibited icv and ip CRF-induced-FPO. The antagonists also prevented the development of nociceptive hyper-responsivity to repeated CRD. These data demonstrate that topology 2 CRF1 antagonists, NGD 98-2 and NGD 9002, administered orally, prevented icv CRF-induced colonic secretomotor stimulation, reduced acute WAS-induced defecation and blocked the induction of visceral sensitization to repeated CRD.